Overexpression of Glutamate Decarboxylase in Mesenchymal Stem Cells Enhances Their Immunosuppressive Properties and Increases Gaba and Nitric Oxide Levels - Rojas-Montecinos, P (Public Library of Science, 2016)
The neurotransmitter GABA has been recently identified as a potent immunosuppressive agent that targets both innate and adaptive immune systems and prevents disease progression of several autoimmunity models. Mesenchymal stem cells (MSCs) are self-renewing progenitor cells that differentiate into various cell types under specific conditions, including neurons. In addition, MSC possess strong immunosuppressive capabilities. Upon cytokine priming, undifferentiated MSC suppress T-cell proliferation via cell-to-cell contact mechanisms and the secretion of soluble factors like nitric oxide, prostaglandin E2 and IDO. Although MSC and MSC-derived neuron-like cells express some GABAergic markers in vitro, the role for GABAergic signaling in MSC-mediated immunosuppression remains completely unexplored. Here, we demonstrate that pro-inflammatory cytokines selectively regulate GAD-67 expression in murine bone marrow-MSC. However, expression of GAD-65 is required for maximal GABA release by MSC. Gain of function experiments using GAD-67 and GAD-65 co-expression demonstrates that GAD increases immunosuppressive function in the absence of pro-inflammatory licensing. Moreover, GAD expression in MSC evokes an increase in both GABA and NO levels in the supernatants of co-cultured MSC with activated splenocytes. Notably, the increase in NO levels by GAD expression was not observed in cultures of isolated MSC expressing GAD, suggesting crosstalk between these two pathways in the setting of immunosuppression. These results indicate that GAD expression increases MSC-mediated immunosuppression via secretion of immunosuppressive agents. Our findings may help reconsider GABAergic activation in MSC for immunological disorders. © 2016 Urrutia et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.